Ethical decision making in social research : a practical guide - Iphofen, Ron. (New York, United States : Palgrave Macmillan, 2011)
This practical, user-friendly guide examines ethics in research. It helps researchers to manage ethical dilemmas that arise while research is being planned, conducted and reported and includes a unique 'ethical review checklist', as well as other useful features, to aid ethics in practice
Includes bibliographical references (p. 216-225) and index.
Keywords: Social sciences -- Research -- Moral and ethical aspects; Decision making -- Moral and ethical aspects